The lineaments of Islam : studies in honor of Fred McGraw Donner - Donner, Fred McGraw, 1945-; Cobb, Paul M., 1967- (Islamic History and Civilization, 2012)
In honor of Fred M. Donner's long and distinguished career as one of the foremost interpreters of early Islam, this volume collects more than a dozen original studies by his students. They range over a wide array of sub-fields in Islamic history and Islamic studies, including early history, historiography, Islamic law, religious studies, Qur'anic studies and Islamic archaeology. The book also includes a bibliography of Donner's works and a biographical sketch of sorts. Taken together, these essays are a clear testament to Donner's wide-ranging and continuing impact on the field. Contributors include: Sean W. Anthony, Jonathan A. C. Brown, David Cook, Vaness De Gifis, Asa Eger, Tracy Hoffman, Marion H. Katz, Kathryn M. Kueny, Shari Lowin, Jens Scheiner, Robert Schick, Stuart Sears, Elizabeth Urban, Tasha Vorderstrasse, Brannon Wheeler, and Hayrettin Yücesoy.